2011
DOI: 10.1152/jn.01046.2010
|View full text |Cite
|
Sign up to set email alerts
|

Receptive field center size decreases and firing properties mature in ON and OFF retinal ganglion cells after eye opening in the mouse

Abstract: Koehler CL, Akimov NP, Rentería RC. Receptive field center size decreases and firing properties mature in ON and OFF retinal ganglion cells after eye opening in the mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 41 publications
(56 reference statements)
3
40
0
Order By: Relevance
“…Their spectral behavior is similar to that of most murine RGCs (Ekesten et al, 2000; Wang et al, 2011) with excitatory drive from both S and M cone opsins but enhanced S-cone input in the ventral retina. Their receptive fields are large, with center diameters ~6-10 degrees of visual angle, among the largest observed among murine RGCs (Koehler et al, 2011). This corresponds well with their dendritic-field dimensions, as has been observed in ganglion cells generally and alpha-like cells in particular (Peichl, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Their spectral behavior is similar to that of most murine RGCs (Ekesten et al, 2000; Wang et al, 2011) with excitatory drive from both S and M cone opsins but enhanced S-cone input in the ventral retina. Their receptive fields are large, with center diameters ~6-10 degrees of visual angle, among the largest observed among murine RGCs (Koehler et al, 2011). This corresponds well with their dendritic-field dimensions, as has been observed in ganglion cells generally and alpha-like cells in particular (Peichl, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Spike waveforms recorded by each electrode were sorted into single units in Offline Sorter (Plexon, Dallas, TX) (Koehler et al 2011;Nirenberg et al 2001;Tian and Copenhagen 2003). Briefly, a threshold of 68 V was used to detect action potentials, the first and second principal components calculated, and clusters formed with action potentials having similar principal components (Elstrott et al 2008;Tian and Copenhagen 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Linear RF studies have provided insight into space-time processing of the center, but the surround has often been ignored, partially due to inability to detect it (Kerschensteiner et al, 2008; Koehler et al, 2011). A recent study in mouse found that blockage of the ON crossover pathway did not alter the chromatic surround of JamB-RGCs (J-RGCs) which was proposed to be driven primarily by horizontal cells (Joesch and Meister, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We used white noise mapping and calculated the geometric mean, similar to other reports and our normal sizes are within their reported measurements (Della Santina et al, 2013). Other reports used different stimulation protocols (gratings, spots, etc) and different calculation methods (hypotenuse, area; Koehler et al, 2011). …”
Section: Discussionmentioning
confidence: 99%